Exploring the relative age effect in Canadian interuniversity ice hockey - Chittle, L.; Horton, S.; Dixon, J. C. (Talent Development & Excellence, 2015)
Relative age effects (RAE) advantage individuals born earlier and disadvantage those born later relative to a cut-off date in a selection year. Studentathletes beginning university with their age cohort are classified as `on-time,` while those entering with a younger cohort are considered to be `delayed.` Birthdates and eligibility years for male and female Canadian Interuniversity Sport (CIS) hockey players were analyzed. Our results revealed a significant RAE among our overall sample of male and female athletes. Further analyses indicated that 99.8% of male and 29.2% of female athletes were delayed. Significantly more delayed male athletes were born in the early months of the selection year than the latter. It appears that relatively younger athletes need to delay to equalize the playing field.